Morphogenetic theory of mental and cognitive disorders: the role of neurotrophic and guidance molecules - Primak, Alexandra; Bozov, Kirill; Rubina, Kseniya; Dzhauari, Stalik; Neyfeld, Elena; Illarionova, Maria; Semina, Ekaterina; Sheleg, Dmitriy; Tkachuk, Vsevolod; Karagyaur, Maxim (Frontiers in Molecular Neuroscience, 2024)
Mental illness and cognitive disorders represent a serious problem for the modern society. Many studies indicate that mental disorders are polygenic and that impaired brain development may lay the ground for their manifestation. Neural tissue development is a complex and multistage process that involves a large number of distant and contact molecules. In this review, we have considered the key steps of brain morphogenesis, and the major molecule families involved in these process. The review provides many indications of the important contribution of the brain development process and correct functioning of certain genes to human mental health. To our knowledge, this comprehensive review is one of the first in this field. We suppose that this review may be useful to novice researchers and clinicians wishing to navigate the field.